PEMBELAJARAN COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) TERHADAP KEMAMPUAN NUMERASI DALAM MENYELESAIKAN SOAL PEMECAHAN MASALAH - Indika Aprillia Fitriana; Andinasari Andinasari; Rahma Siska Utari (Program Studi PGSD Universitas Flores, 2023)
Current mathematics education should meet requirements that involve critical thinking skills, real-world relevance, the use of technology, and communication and collaboration abilities. In this regard, students need to have good numeracy skills, which involve the ability to use numbers and mathematical symbols in everyday problem-solving, such as calculations and data interpretation. Numeracy skills are important in shaping responsible and competent individuals. Additionally, problem-solving strategies are also at the core of mathematics teaching. Research has shown that the use of the Cooperative Integrated Reading and Composition (CIRC) instructional model has positive consequences for mathematical problem-solving proficiency. With the CIRC model, students can effectively improve their numeracy skills and mathematical problem-solving strategies. This research was conducted using a quantitative method, t-test, and paired sample test. The research subjects consisted of 50 eighth-grade students at SMP Negeri 7 Tungkal Jaya. Data was collected through documents, observations, and tests. Data analysis was done by conducting a paired sample t-test to assess the significance of the influence of CIRC learning on students' problem-solving competence. It is important to conduct further research involving larger samples and considering factors that may potentially affect learning outcomes.